Kemampuan Number Sense Siswa dalam Menyelesaikan Masalah Operasi Bilangan Ditinjau dari Perbedaan Kemampuan Matematika - Zainal; Perdanawati, Shanty Galuh (FKDP (Forum Komunikasi Dosen Peneliti), 2025)
Number sense is a fundamental component of meaningful mathematics learning, particularly in solving arithmetic operation problems. However, many students demonstrate procedural proficiency without adequate numerical understanding. This study aims to describe and analyze students’ number sense in solving arithmetic operation problems in relation to differences in mathematical ability. A mixed methods approach with an explanatory sequential design was employed. The participants were 60 seventh-grade students from MTs Miftahul Ulum Lumajang, who were categorized into high, medium, and low mathematical ability groups based on a mathematics ability test. Quantitative data were collected through a number sense test and analyzed using descriptive statistics and one-way ANOVA, while qualitative data were obtained through in-depth interviews and analyzed using the interactive model of Miles, Huberman, and Saldaña. The results indicate a statistically significant difference in students’ number sense across different levels of mathematical ability (p<0.05). Students with high mathematical ability demonstrated more developed number sense, characterized by effective estimation, flexible strategy use, and the ability to evaluate the reasonableness of results. Students with medium mathematical ability showed partial development with inconsistent use of estimation and strategies, whereas students with low mathematical ability relied heavily on mechanical procedures and exhibited limited understanding of numerical relationships. These findings highlight the importance of differentiated instruction in arithmetic operations that emphasizes the development of number sense according to students’ mathematical ability levels.